Possibilities of parliamentary supervision of the independent judiciary with reference to the sub judice doctrine: independent judiciary - Janjić, Sandra (Glasnik Advokatske komore Vojvodine, 2024)
In functioning democracies, the existence of an effective system of mutual checks and balances and respect for the rule of law are essential to ensure an appropriate balance between the three pillars of government, namely the judiciary, the executive and the legislature.Parliamentary oversight is a basic component of the system of checks and balances that seeks to ensure justice and the rule of law in democratic societies. The basic purpose of all courts is to provide fair justice to all citizens. Therefore, there is a need to ensure that only one court deals with a particular case at a time in accordance with the doctrine of subjudice. In recent times, this doctrine has gained much greater importance because it plays a vital role in the proper functioning of the judicial machinery in the country. Sub judice basically means ’a matter that is still pending before the Court’ or the lawsuit is still pending. The principle simultaneously represents a guarantor of the independence of the judiciary, but also a framework for achieving effective parliamentary supervision and balance.